Corporate social responsibility: exploring stakeholder relationships and programme reporting across leading FTSE companies - Knox, Simon; Maklan, Stan; French, P. (Springer Science Business Media, 2005)
Although it is now widely recognised by business leaders that their companies need to accept a broader responsibility than short-term profits, recent research suggests that as corporate social responsibility (CSR) and social reporting become more widespread, there is little empirical evidence of the range of stakeholders addressed through their CSR programmes and how such programmes are reported. Through a CSR framework which was developed in an exploratory study, we explore the nature of stakeholder relationships reported across leading FTSE companies and the importance they attach to communicating both social and business outcomes. It is evident from the hypotheses tested that the bigger FTSE companies, particularly extraction companies and telecoms, are more adept at identifying and prioritising their stakeholders, and linking CSR programmes to business and social outcomes. However, we draw the general conclusion that building stronger stakeholder relationships through CSR programmes – other than with customers – is not currently a priority for most companies. We also conclude that a limited sophistication in managing multiple stakeholders may compromise the impact of CSR upon business and social results. Finally, the managerial implications and the contribution of our study are discussed before closing with an acknowledgement of the limitations of this work and suggestions for further resea